2016
DOI: 10.17795/ijcp-3704
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cytomegalovirus Antibodies and Primary Infection among Women and Infants in Iran: A Meta-Analysis

Abstract: Background: Seroprevalence of Cytomegalovirus infection varies between 40% and 100% worldwide. Different studies carried out in Iran indicate this variation in this country. It is important to estimate the total infection prevalence using a reliable method such as meta-analysis in order to be applied by policymakers. This study aims to estimate the IgG and IgM seroprevalences of CMV infection among Iranian women and neonates. Method:We selected eligible articles for final meta-analysis by searching the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[2,6,7] The anti-CMV IgG prevalence in the general population (Group B) was 75.2% which was also comparable to the previous studies. [8][9][10] Looking at the age distribution of the anti-CMV IgG-positive cases in Group A, 46 (92%) cases were in the age group of >40-60 years, 43 (86%) cases were in the age group of 18-40 years, and 21 (84%) cases were in the age group of >60-85 years. The previous authors have also reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…[2,6,7] The anti-CMV IgG prevalence in the general population (Group B) was 75.2% which was also comparable to the previous studies. [8][9][10] Looking at the age distribution of the anti-CMV IgG-positive cases in Group A, 46 (92%) cases were in the age group of >40-60 years, 43 (86%) cases were in the age group of 18-40 years, and 21 (84%) cases were in the age group of >60-85 years. The previous authors have also reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…In general female population CMV IgG seroprevalence is 51.7-95.7%, while the IgM seroprevalence is 4.1 to 6.3%, while in women with bad obstetric history (BOH) the CMV IgG seroprevalence is with a range of 91.2% -96.6% and 3.8% to 9.46% for IgM seroprevalence [15][16][17][18][19]. The association between CMV infection and age is with conflicting results, however, some study suggest that CMV infection is increased in women with age [16].…”
Section: High-risk Womenmentioning
confidence: 99%